Adsorption material for sewage treatment

Through the combination of HACC@Cu-MOF and aerogel composite materials, the problem of low removal efficiency of heavy metal ion in existing wastewater treatment technology is solved, and the sewage treatment effect with efficient adsorption and stable structure is achieved.

CN119303550APending Publication Date: 2025-01-14ANHUI MEIZIRAN ENVIRONMENTAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411763434.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing wastewater treatment technologies are difficult to effectively remove heavy metal ions, such as chromium, copper and lead, and the pore size of the silicon oxide aerogel balls is too small, resulting in limited application in the wastewater treatment field.

Method used

HACC@Cu-MOF and aerogel composite material are used to modify the combination of MOF materials and aerogels through quaternary ammonium salt chitosan to form an adsorption material with porous structure and stability characteristics, enhancing the adsorption ability of heavy metal ions.

Benefits of technology

It has achieved efficient adsorption of heavy metal ions such as Pb2+, Cu2+, Cr6+, and has high adsorption efficiency and stable structure, which has significantly improved the sewage treatment effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an adsorption material for sewage treatment, and belongs to the field of sewage treatment. The adsorption material is formed by compounding a quaternary ammonium salt chitosan-MOF material and aerogel. The preparation method comprises the following steps: quaternizing chitosan to obtain quaternary ammonium salt chitosan, modifying an MOF material with the quaternary ammonium salt chitosan to obtain HACC-coated Cu-MOF, and compounding the HACC-coated Cu-MOF and aerogel to obtain the adsorption material HACC-coated Cu-MOF-aerogel. The HACC-coated Cu-MOF has the characteristics of good adsorbability to heavy metal ions, porosity and stable structure, and is combined with the characteristics of large adsorption capacity and high adsorption efficiency of aerogel, so that the adsorption material with high adsorption efficiency and stable structure is prepared, and sewage containing heavy metals such as Pb < 2 + >, Cu < 2 + > and Cr < 6 + > is treated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage treatment, and in particular to an adsorption material for sewage treatment. Background Art

[0002] With the continuous acceleration of urbanization, the problem of heavy metal pollution in water bodies has attracted more and more attention. The high toxicity of heavy metals has caused serious harm to the environment and organisms. Among them, chromium, copper, lead and other metals are the most prominent. How to remove these metal ions from wastewater is an urgent problem to be solved.

[0003] As a new type of nano-scale porous carbon material, carbon aerogel has the advantages of high porosity, large specific surface area, and wide density range. Because its continuous three-dimensional nano-network structure can be controlled within the mesoscopic size, it is widely used in catalyst carriers, electrodes of supercapacitors, thermal insulation materials, adsorbents, etc. However, the three-dimensional network structure of aerogel has small pores and obvious capillary action. During the application process, the gas-liquid interfacial tension easily causes the pore structure to collapse.

[0004] A patent application with publication number CN 103880025A discloses a method for preparing silica aerogel beads at normal pressure. The silica aerogel beads prepared by the invention have a fast adsorption rate, a large adsorption capacity, and are easy to use. They can be used for sewage treatment and air purification. In addition, the preparation process is stable and the silica aerogel beads are low in cost. They can provide a practical source of raw materials for the large-scale production of thermal insulation materials, industrial catalysts, and chromatographic column filling materials. However, the pore size of the aerogel beads prepared by the invention is too small, and the scope of application in the field of sewage treatment is limited. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide an adsorption material for sewage treatment, which has a large adsorption capacity, good adsorption efficiency and a stable structure.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] An adsorption material for sewage treatment, characterized in that it is composited with HACC@Cu-MOF and aerogel;

[0008] The adsorption material is HACC@Cu-MOF-aerogel, and the composite steps are as follows:

[0009] (1) adding 25-35 parts of resorcinol, 10-15 parts of furfural and 0.6-1.2 parts of ethylenediamine by weight into deionized water, stirring at 65° C. and 1000-1200 rpm for 3-5 minutes to obtain an aerogel solution;

[0010] (2) 30-40 parts by weight of HACC@Cu-MOF were added to the aerogel solution, ultrasonically mixed at 65°C for 30 min, then frozen at -15°C, solvent exchanged with isopropanol at 25°C, and dried at 45°C to obtain HACC@Cu-MOF-aerogel.

[0011] Furthermore, the HACC@Cu-MOF is prepared by the following steps:

[0012] 1) quaternizing chitosan to obtain quaternary ammonium salt chitosan: dissolving chitosan in isopropanol, and adjusting the pH of the chitosan solution to 8 with 1M NaOH; adding 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution, stirring at a constant temperature of 60°C-90°C for 6h-10h, filtering, washing with anhydrous ethanol, and drying to obtain HACC;

[0013] 2) Modifying MOF material with quaternary ammonium salt chitosan to obtain HACC@Cu-MOF: HACC was dissolved in acetic acid, and then copper salt was added to the HACC solution. After stirring until completely dissolved, the solution was dropped into a 1M NaOH solution. The solution was allowed to stand for 5-6 hours, filtered, and washed with deionized water until neutral to obtain Cu-HACC; Cu-HACC and organic ligand were added to DMF and heated to reflux for 70-72 hours; HACC@Cu-MOF was obtained by centrifugal washing with DMF and vacuum drying.

[0014] Furthermore, in step 1), the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:2-4.

[0015] Furthermore, the copper salt in step 2) is one of Cu(NO3)2·3H2O, CuSO4·5H2O, and CuCl2·2H2O.

[0016] Furthermore, the organic ligand in step 2) is one of 2-aminoterephthalic acid, terephthalic acid, and 1,3,5-trimethylbenzene carboxylic acid.

[0017] Furthermore, in step 2), the usage ratio of HACC and copper salt is 1.5 g:10 mmol.

[0018] Furthermore, in step 2), the usage ratio of Cu-HACC to the organic ligand is 10 g:10 mmol.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention prepares an adsorbent material for sewage treatment, which is a composite of HACC@Cu-MOF and aerogel; HACC@Cu-MOF has good adsorption for heavy metal ions, and has the characteristics of being porous and having a stable structure; the aerogel has a large adsorption capacity and high adsorption efficiency, but the pores in the three-dimensional network structure of the aerogel are small, and the capillary effect is obvious. During the application process, the gas-liquid interfacial tension easily causes the pore structure to collapse; the composite of HACC@Cu-MOF and aerogel can prepare an adsorbent material with high adsorption efficiency and a stable structure, which is effective for treating wastewater containing Pb 2+ , Cu 2+ Cr 6+ It has excellent adsorption effect on sewage containing heavy metals.

[0021] (2) The present invention uses quaternary ammonium salt chitosan. Compared with chitosan, quaternary ammonium salt chitosan has great activity and can more effectively coordinate with heavy metal ions to form more stable complexes. This enhanced coordination ability makes the adsorption effect of quaternary ammonium salt chitosan on heavy metal ions more significant; in addition, quaternary ammonium salt chitosan has better water solubility and dispersibility, which helps the adsorption material to be evenly distributed in sewage and fully contact with heavy metal ions, thereby improving the adsorption efficiency. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The adsorption materials obtained in the embodiments of the present invention and the comparative examples are used to treat a Pb-containing 2+ , Cu 2+ Cr 6+ Heavy metal ion wastewater; Pb in wastewater 2+ , Cu 2+ Cr 6+ The concentrations are 110mg / L, 108mg / L and 120mg / L respectively; the pH of the sewage is 9.

[0024] Example 1

[0025] This embodiment provides an adsorption material for sewage treatment, characterized in that it is composed of a quaternary ammonium salt chitosan-MOF material and an aerogel;

[0026] Prepared by the following steps:

[0027] (1) Quaternization of chitosan: 1.5 g of chitosan was dissolved in 100 mL of isopropanol, and the pH of the chitosan solution was adjusted to 8 with 1 M NaOH; 3 g of 2,3-epoxypropyltrimethylammonium chloride was added to the chitosan solution, and the mixture was stirred at 80°C for 10 h, filtered, washed with anhydrous ethanol, and dried to obtain HACC.

[0028] (2) HACC modified MOF material: 1.5 g HACC was dissolved in 50 mL acetic acid, and then 2.42 g Cu(NO3)2·3H2O was added to the HACC solution. After stirring until completely dissolved, the solution was dropped into 300 mL 1 M NaOH solution. The solution was allowed to stand for 6 h, filtered, and washed with deionized water until neutral to obtain Cu-HACC. 10 g Cu-HACC and 1.81 g 2-aminoterephthalic acid were added to DMF and heated under reflux for 70-72 h. HACC@Cu-MOF was obtained by centrifugal washing with DMF and vacuum drying.

[0029] (3) HACC@Cu-MOF and aerogel composite:

[0030] 1) adding 30 parts of resorcinol, 12 parts of furfural and 1 part of ethylenediamine by weight into deionized water, stirring at 65° C. and 1200 rpm for 5 minutes to obtain an aerogel solution;

[0031] 2) 30 parts of HACC@Cu-MOF were added to the aerogel solution by weight, and after ultrasonic mixing at 65°C for 30 min, the solution was frozen at -15°C, solvent exchanged with isopropanol at 25°C, and dried at 45°C to obtain the adsorption material HACC@Cu-MOF-aerogel.

[0032] Example 2

[0033] Compared with Example 1, the difference between this embodiment and Example 1 is that the steps "dissolve 1.5 g of chitosan in 100 mL of isopropanol, and adjust the pH of the chitosan solution to 8 with 1 M NaOH; add 3 g of 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution" in step (1) is changed to "dissolve 1.5 g of chitosan in 100 mL of isopropanol, and adjust the pH of the chitosan solution to 8 with 1 M NaOH; add 4.5 g of 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0034] Example 3

[0035] Compared with Example 1, the difference between this embodiment and Example 1 is that the step (1) of "dissolving 1.5 g of chitosan in 100 mL of isopropanol, and adjusting the pH of the chitosan solution to 8 with 1 M NaOH; adding 3 g of 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution" is changed to "dissolving 1.5 g of chitosan in 100 mL of isopropanol, and adjusting the pH of the chitosan solution to 8 with 1 M NaOH; adding 6 g of 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution"; the remaining raw materials and preparation process remain the same as those in Example 1.

[0036] Example 4

[0037] Compared with Example 2, this example is different in that "adding 30 parts by weight of HACC@Cu-MOF to the aerogel solution" in step 2) is changed to "adding 35 parts by weight of HACC@Cu-MOF to the aerogel solution"; the remaining raw materials and preparation process remain the same as in Example 2.

[0038] Example 5

[0039] Compared with Example 2, this example is different in that "adding 30 parts by weight of HACC@Cu-MOF to the aerogel solution" in step 2) is changed to "adding 40 parts by weight of HACC@Cu-MOF to the aerogel solution"; the remaining raw materials and preparation process remain the same as in Example 2.

[0040] Comparative Example 1

[0041] Compared with Example 1, the difference between this comparative example is that chitosan is not quaternized by using quaternary ammonium salt, and chitosan is directly used to prepare the adsorption material CS@Cu-MOF-aerogel; the other raw materials and preparation process remain the same as those in Example 1.

[0042] Comparative Example 2

[0043] The difference between this comparative example and Example 1 is that HACC@Cu-MOF is used alone as the adsorption material; the other raw materials and preparation process remain the same as those in Example 1.

[0044] Comparative Example 3

[0045] Compared with Example 1, this comparative example differs in that aerogel is used alone as the adsorption material;

[0046] The aerogel preparation steps include: adding 30 parts of resorcinol, 12 parts of furfural and 1 part of ethylenediamine by weight into deionized water, stirring at 65°C and 1200 rpm for 5 minutes to obtain an aerogel solution; freezing the aerogel solution at -15°C, performing solvent exchange with isopropanol at 25°C, and drying at 45°C to obtain an aerogel.

[0047] Comparative Example 4

[0048] Compared with Example 1, this comparative example is different in that HACC@Cu-MOF and aerogel are not compounded, HACC@Cu-MOF and aerogel are directly used as adsorption materials, and the aerogel preparation process is the same as that of Comparative Example 3; the other raw materials and preparation process remain the same as those of Example 1.

[0049] The pH of the heavy metal wastewater was adjusted to 6 by hydrochloric acid and ammonia water, and then the adsorption materials obtained in Examples 1 to 5 and Comparative Examples 1 to 4 were added to the wastewater, and the amount of adsorption materials added was 2 g / L. The mixture was stirred for 3 h at room temperature and filtered for separation. The Pb content in the filtrate was then determined by ICP-OES. 2+ , Cu 2+ Cr 6+ The concentration of Pb can be calculated by 2+ , Cu 2+ Cr 6+ The removal rate; the results are shown in Table 1:

[0050] Table 1

[0051] Removal rate (%) <![CDATA[Pb 2+ ]]> <![CDATA[Cu 2+ ]]> <![CDATA[Cr 6+ ]]> Example 1 97.27 97.35 97.12 Example 2 98.25 98.23 98.35 Example 3 97.31 97.37 97.22 Example 4 99.11 99.12 99.14 Example 5 99.82 99.83 99.81 Comparative Example 1 91.34 91.26 91.41 Comparative Example 2 82.85 82.54 83.21 Comparative Example 3 79.61 79.23 79.54 Comparative Example 4 80.76 80.63 81.12

[0052] It can be seen from Table 1 that the adsorption of Pb in sewage by the adsorbents of Examples 1 to 5 is 2+ , Cu 2+ Cr 6+ The removal rate reached more than 97%, with excellent adsorption effect; compared with Example 1, Example 2, and Example 3, the adsorbent obtained when the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride was 1:3 had a better adsorption effect, indicating that the amount of quaternary ammonium salt should not be too little or too much when quaternizing chitosan. When the amount of quaternary ammonium salt is too little, the degree of quaternization will be low, that is, the number of quaternary ammonium groups introduced into the chitosan molecule is limited. When the amount of quaternary ammonium salt is too much, the presence of the product grafted chain will cause the steric hindrance to gradually increase, making the reaction difficult. Compared with Example 2, Example 4, and Example 5, increasing the amount of HACC@Cu-MOF in the HACC@Cu-MOF-aerogel composite material can improve the adsorption effect of the adsorbent material.

[0053] Comparison between Example 1 and Example 1 shows that the use of CS@Cu-MOF-aerogel as an adsorption material for Pb 2+ , Cu 2+ Cr 6+The removal rate is low and the adsorption effect is poor because compared with chitosan, quaternary ammonium chitosan has great activity and can more effectively coordinate with heavy metal ions to form more stable complexes. This enhanced coordination ability makes the adsorption effect of quaternary ammonium chitosan on heavy metal ions more significant; in addition, quaternary ammonium chitosan has better water solubility and dispersibility, which helps the adsorption material to be evenly distributed in the sewage and fully contact with heavy metal ions, thereby improving the adsorption efficiency.

[0054] Compared with Example 1, Comparative Examples 2, 3 and 4 show that the 2+ , Cu 2+ Cr 6+ The removal rates are all low, indicating that using HACC@Cu-MOF alone, aerogel alone, and directly using HACC@Cu-MOF and aerogel as adsorption materials cannot achieve good adsorption effects.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An adsorbent material for sewage treatment, characterized in that: Composited from HACC@Cu-MOF and aerogel; The adsorption material is HACC@Cu-MOF-aerogel, and the composite steps are as follows: (1) adding 25-35 parts of resorcinol, 10-15 parts of furfural and 0.6-1.2 parts of ethylenediamine by weight into deionized water, stirring at 65° C. and 1000-1200 rpm for 3-5 minutes to obtain an aerogel solution; (2) 30-40 parts by weight of HACC@Cu-MOF were added to the aerogel solution, ultrasonically mixed at 65°C for 30 min, then frozen at -15°C, solvent exchanged with isopropanol at 25°C, and dried at 45°C to obtain HACC@Cu-MOF-aerogel.

2. The adsorption material for sewage treatment according to claim 1, characterized in that: The HACC@Cu-MOF is prepared by the following steps: 1) quaternizing chitosan to obtain quaternary ammonium salt chitosan: dissolving chitosan in isopropanol, and adjusting the pH of the chitosan solution to 8 with 1M NaOH; adding 2,3-epoxypropyltrimethylammonium chloride to the chitosan solution, stirring at a constant temperature of 60°C-90°C for 6h-10h, filtering, washing with anhydrous ethanol, and drying to obtain HACC; 2) Modifying MOF material with quaternary ammonium salt chitosan to obtain HACC@Cu-MOF: HACC was dissolved in acetic acid, and then copper salt was added to the HACC solution. After stirring until completely dissolved, the solution was dropped into a 1M NaOH solution. The solution was allowed to stand for 5-6 hours, filtered, and washed with deionized water until neutral to obtain Cu-HACC; Cu-HACC and organic ligand were added to DMF and heated to reflux for 70-72 hours; HACC@Cu-MOF was obtained by centrifugal washing with DMF and vacuum drying.

3. The adsorbent material for sewage treatment according to claim 2, characterized in that: The mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride in step 1) is 1:2-4.

4. The adsorbent material for sewage treatment according to claim 2, characterized in that: The copper salt in step 2) is one of Cu(NO3)2·3H2O, CuSO4·5H2O, and CuCl2·2H2O.

5. The adsorbent material for sewage treatment according to claim 2, characterized in that: The organic ligand in step 2) is one of 2-aminoterephthalic acid, terephthalic acid, and 1,3,5-trimethylbenzene carboxylic acid.

6. The adsorbent material for sewage treatment according to claim 2, characterized in that: The usage ratio of HACC and copper salt in step 2) is 1.5 g:10 mmol.

7. The adsorbent material for sewage treatment according to claim 2, characterized in that: In step 2), the usage ratio of Cu-HACC and organic ligand is 10 g:10 mmol.

Citation Information

Patent Citations

  • Method for preparing silicon oxide aerogel pellet at normal pressure at normal pressure

    CN103880025A